THE RELATIONSHIP OF FAMILY SUPPORT MEDICATION ADHERENCE IN PATIENTS WITH LEPROSY IN THE HEALT WORK PRAGAAN SUMENEP - Anshori, Faisal; Azizah, Umi; Kusyani, Asri (WELL BEING, 2016)
Leprosy is an infectious disease that can cause disability for the sufferer but leprosy can recovered by way of medication on a regular basis without interruption. However, in Sumenep still some leprosy patients who do not adhere to the treatment of leprosy with the reason for being lazy, bored, can not be cured. This is likely caused by factors that are lacking in family support doing therapeutic treatment The purpose of this study was to determine the relationship of family support medication adherence in patients with leprosy m the health work Pragaan Sumenep. This study design using analytic correlational with cross sectional approach. The population of leprosy patients m the health work Pragaan Sumenep numbering 36 people, total sampling technique sampling obtained a sample of 36 people. Collecting data using questionnaires, statistical analysis using Spearman Rank Correlation test with standard significant (0.05). The result showed almost entirely good support as many as 31 people (86.1%) and a small enough support as many as five people (13.9%). Based on statistical test there is a relationship with the family support medication adherence in patients with leprosy ie, p = 0.027 (p<a=0,05). Increasingly lepers obediently taking the drug, the faster the leprosy cured. Keywords: Family Support, Camphene taking medication, Leprosy